2022
DOI: 10.31940/jasl.v6i2.646
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive strategy to enhance students' reading text-ability: case study in the vocational high school

Abstract: This study aims to determine: the process of implementing metacognitive strategies in learning reading skills. The case study research method is used in this study. The results of this study indicate that the implementation of metacognitive strategies applies three stages, namely: 1) self-planning, 2) self-monitoring, and 3) self-evaluation. These stages are carried out by creating a pleasant relationship with students through discussion. The students were highly motivated by the learning process and five stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It was seen that the cognitive awareness strategy positively increased students' cognitive awareness skills, reading comprehension success and students' attitudes towards the course during the Turkish Language Course. Faridah, Setyaningrum, and Falakha (2022) examined whether the metacognitive strategy instruction "CALLA" affects students' reading comprehension and reading awareness, and it was observed that students to whom the metacognitive strategy method was applied had significantly higher scores. In the study of Aktaş (2013), in which the effect of attitude and metacognitive skills on the academic achievement level of the Turkish Language Course of students studying in the Primary Education Department of Classroom Teaching at the Faculty of Education was examined, it was revealed that the academic achievement level of the Turkish Language Course was positively affected.…”
Section: Resultsmentioning
confidence: 99%
“…It was seen that the cognitive awareness strategy positively increased students' cognitive awareness skills, reading comprehension success and students' attitudes towards the course during the Turkish Language Course. Faridah, Setyaningrum, and Falakha (2022) examined whether the metacognitive strategy instruction "CALLA" affects students' reading comprehension and reading awareness, and it was observed that students to whom the metacognitive strategy method was applied had significantly higher scores. In the study of Aktaş (2013), in which the effect of attitude and metacognitive skills on the academic achievement level of the Turkish Language Course of students studying in the Primary Education Department of Classroom Teaching at the Faculty of Education was examined, it was revealed that the academic achievement level of the Turkish Language Course was positively affected.…”
Section: Resultsmentioning
confidence: 99%
“…After that, the teacher implements learning using metacognitive strategies. Metacognitive strategies have been proven to be effective in improving language skills (Faridah et al, 2022); (Ramadhanti & Yanda, 2021); (Tawarik et al, 2021). During learning using metacognitive strategies, students can monitor their writing performance using a reflective journal.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the symbiotic relationship between English reading learning strategies and metacognitive strategies is instrumental for educators and learners alike [11] . Through the adept amalgamation of these strategies, learners have the potential to bolster their comprehension, adaptability, and overall proficiency in reading English, thereby cultivating a more nuanced understanding of the language [6] .…”
Section: Relationship With Metacognitive Strategiesmentioning
confidence: 99%